A kind of water-based supramolecular adhesion material and preparation method thereof
By using the aqueous supramolecular adhesive material constructed by heterocyclic aromatic acyl amino acids and cationic polyelectrolytes, the problem of insufficient performance and safety of existing medical adhesives is solved, and the effect of high bond strength and good biocompatibility is achieved.
Patent Information
- Application Number
- CN202110260837.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-10
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-03-10
AI Technical Summary
Existing medical adhesives have not yet met the higher requirements of clinical medicine in the fields of performance, safety and application, and the preparation process of imitation mussel adhesive materials is complex and requires toxic reagents.
The aqueous supramolecular adhesive material constructed with heterocyclic aromatic acyl amino acids and cationic polyelectrolytes is obtained by a simple preparation method in aqueous solvents.
It achieves high bonding strength, good mechanical properties, biocompatibility and safety, is suitable for medical and industrial fields, and the preparation process is green and environmentally friendly and has low cost.
Smart Images

Figure 1 
Figure BDA0002969895980000021 
Figure BDA0002969895980000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and specifically relates to a novel condensate-based adhesive material and a preparation method thereof, in particular to an adhesive material based on heterocyclic aromatic acyl amino acid and cationic polyelectrolyte and a preparation method thereof. Background Art
[0002] At present, adhesives play an important role in many fields such as industry, medicine (wound dressings) and daily life. Adhesives can be roughly divided into two categories: adhesive type and tape type. The former is a liquid solution (condensate, polymer solution, etc.) that requires a curing process to achieve interfacial bonding; the latter is a solid material (polymer film, hydrogel, etc.) that can be directly adhered to the substrate.
[0003] Among them, medical adhesive is a medical material used for wound hemostasis, healing, and preventing fluid leakage. Compared with traditional surgical suturing methods, it is simple to operate, shortens the operation time, and is conducive to rapid tissue recovery, so it has broad application prospects. Since medical adhesives are directly bonded to the organism, the ideal medical adhesive can meet the requirements of safety, non-toxicity, non-carcinogenicity, non-teratogenicity, non-mutagenicity, good bonding strength, rapid bonding with tissues at room temperature and pressure, good biocompatibility, sterility and antibacterial properties, simple operation, low heat generation during curing to avoid scalding tissues, etc. Although traditional tissue adhesives have been approved as a means of closing certain specific surgical wounds, the performance, safety and limitations of the adhesives currently used cannot meet the higher requirements of clinical medicine.
[0004] In the study of adhesives, mussels can quickly adhere to different solid substrates in seawater. Studies have shown that mussel adhesive proteins contain a large amount of 3,4-dihydroxyamphetamine (dopamine), which is the key to the good anti-wet adhesion of mussel adhesive proteins. The study of simulating the mussel adhesion process to prepare mussel-like adhesive materials has attracted widespread attention from researchers and can also be used for underwater adhesion. However, most of these bionic materials require a cumbersome synthesis process, need to be prepared under harsh conditions, and require the use of initiators, cross-linking agents and toxic reagents.
[0005] Therefore, it remains challenging to develop low-cost adhesive materials with simple preparation methods, biocompatibility and strong adhesion ability to various substrates. Summary of the invention
[0006] To solve the above problems, the inventors conducted intensive research and obtained an adhesive material constructed by using a heterocyclic aromatic acyl amino acid containing an electron-donating group and a cationic polyelectrolyte. The material has a simple preparation method, is safe, non-toxic, has good biocompatibility, high bonding strength, good mechanical properties, is not affected by moisture and oil solubility, and can be used in medicine and other industrial fields.
[0007] The present invention aims to provide a water-based supramolecular adhesive material, wherein the water-based supramolecular adhesive material is prepared from raw materials including heterocyclic aromatic acyl amino acid and cationic polyelectrolyte. The raw materials are prepared in a water solvent to obtain the water-based supramolecular adhesive material.
[0008] The heterocyclic aromatic acyl amino acid comprises a heterocyclic unit with an electron-donating group, an amino aromatic carboxylic acid unit and an amino acid unit. The electron-donating group comprises an oxygen-containing electron-donating group or a nitrogen-containing electron-donating group, preferably a hydroxyl group and an amino group.
[0009] In a preferred embodiment of the present invention, the heterocyclic aromatic acyl amino acid has the following molecular structure formula:
[0010]
[0011] in,
[0012] R1, R2, and R3 are each independently selected from hydrogen or an electron-donating group, preferably selected from hydrogen, an oxygen-containing electron-donating group or a nitrogen-containing electron-donating group, more preferably hydrogen, hydroxyl or amino. In a preferred embodiment of the present invention, one of R1, R2, and R3 is hydrogen, and the other two substituents are electron-donating groups, preferably, R3 is hydrogen, and R1 and R2 are electron-donating groups, for example, R1 is hydroxyl, R2 is amino, and R3 is hydrogen.
[0013] G1, G2, G3, and G4 are each independently selected from hydrogen, C1-C5 alkyl, C1-C5 alkoxy, amino, hydroxy, aldehyde or carboxyl, preferably selected from hydrogen, methyl, ethyl, methoxy, ethoxy, amino or hydroxy, more preferably hydrogen.
[0014] R is selected from hydrogen, alkyl, phenylalkyl, phenolic alkyl, carboxylalkyl, amide alkyl, aminoalkyl, hydroxyalkyl or nitrogen-containing heterocyclic alkyl, preferably selected from hydrogen, phenolic alkyl, carboxylalkyl, amide alkyl, aminoalkyl, hydroxyalkyl, indolyl alkyl or imidazolyl alkyl, more preferably carboxylalkyl. R has a carbon number of 0-4.
[0015] In a preferred embodiment of the present invention, the heterocyclic aromatic acyl amino acid is folic acid.
[0016] The cationic polyelectrolyte is selected from one or more of primary amine type cationic polymers, secondary amine type cationic polymers, tertiary amine type cationic polymers and quaternary ammonium type cationic polymers.
[0017] The present invention also aims to provide a method for preparing an aqueous supramolecular adhesive material, wherein the raw materials for preparation of the method include heterocyclic aromatic acyl amino acids and cationic polyelectrolytes, and the raw materials are dispersed in an aqueous solution for preparation. The method specifically comprises the following steps:
[0018] Step 1, dissolving a heterocyclic aromatic acyl amino acid in water to obtain a solution A;
[0019] Step 2, dissolving the cationic polyelectrolyte in water to obtain solution B;
[0020] Step 3: Mix solution A and solution B to obtain a water-based supramolecular adhesion material.
[0021] Another object of the present invention is to provide the use of the aqueous supramolecular adhesion material, which is used for bonding biological tissues, such as human or animal organs, for example skin, metal materials, such as stainless steel, inorganic materials, such as inorganic glass, wooden materials, plastics, such as polytetrafluoroethylene and polyethylene, and is particularly used for bonding biological tissues in the field of medical surgery.
[0022] The aqueous supramolecular adhesion material and the preparation method thereof provided in the present invention have the following beneficial effects:
[0023] (1) The present invention uses heterocyclic aromatic acyl amino acids and cationic polyelectrolytes as raw materials to prepare supramolecular adhesive materials, which can be used to bond materials of various materials, have strong bonding force, and the adhesive material itself has good mechanical properties.
[0024] (2) The aqueous supramolecular adhesive material of the present invention can be prepared by selecting raw materials with high safety and good biocompatibility. The obtained adhesive material can be used for the adhesion of biological tissues, and thus applied to the fields of medical surgery, and when used in vivo, it can be metabolized and absorbed in the body, therefore, it has good application prospects.
[0025] (3) The preparation of the aqueous supramolecular adhesion material can be carried out in an aqueous solvent under normal temperature and pressure conditions. The preparation method is simple, no complicated synthesis process is required, and the use of toxic and harmful reagents is avoided. The synthesis process is green and environmentally friendly, and the obtained adhesion material is safe and non-toxic and has a wide range of applications.
[0026] (4) The preparation process of the water-based supramolecular adhesive material does not require harsh preparation conditions and special equipment, the material source is wide, the production cost is low, it is conducive to large-scale production, the method of use is simple, and it can be promoted and applied. Especially in the medical field, it is easy to operate, does not release heat, has good adhesion, and is easy to use. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 (a) shows the macroscopic morphology of the wet folic acid-PDDA supramolecular adhesion material in Example 1 of the present invention; Figure 1 (b) is the macroscopic morphology of the folic acid-PDDA supramolecular adhesion film in Example 1; Figure 1 (c) is the SEM test image of folic acid-PDDA supramolecular adhesion film PF-C-9;
[0028] Figure 2 The infrared spectra of folic acid (FA), PDDA and the folic acid-PDDA supramolecular adhesive film PF-C-9-Film obtained in Example 1 of the present invention are shown;
[0029] Figure 3 The graph showing the changes in the storage modulus G' and the loss modulus G" of the wet folic acid-PDDA supramolecular adhesion material prepared in Example 1 of the present invention;
[0030] Figure 4 The shear viscosity variation diagram of the wet folic acid-PDDA supramolecular adhesion material prepared in Example 1 of the present invention is shown;
[0031] Figure 5 The infrared spectrum test diagrams of the wet folic acid-PDDA supramolecular adhesion material PF-C-9 prepared in Example 1 of the present invention and the PF-C-9 adhered to the copper sheet in Experimental Example 4 are shown;
[0032] Figure 6 The tensile strength and elongation at break test graph of the folic acid-PDDA supramolecular adhesion film PF-C-9-Film obtained in Example 1 of the present invention are shown;
[0033] Figure 7 The load-bearing effect diagrams of the adhesive film PF-C-9-Film obtained in Example 1 of the present invention on pig skin, wet glass and 200g stainless steel weight are shown;
[0034] Figure 8 An example diagram of a physical tensile test of the adhesion film folic acid-QCS-Film obtained in Example 2 of the present invention being bonded to pig skin is shown. DETAILED DESCRIPTION
[0035] The present invention is described in detail below through specific implementation modes, and the characteristics and advantages of the present invention will become clearer and more specific with these descriptions.
[0036] The present invention provides an adhesive material prepared by supramolecular assembly using heterocyclic aromatic acyl amino acids containing electron-donating groups such as amino groups and hydroxyl groups and cationic polyelectrolytes as raw materials. The preparation process is simple and no complex synthetic additives, toxic raw materials and organic solvents are used. The obtained adhesive material has good safety and biocompatibility, strong bonding force, and good mechanical properties. The adhesive material itself has broad application prospects in medical adhesives and industrial adhesives.
[0037] The present invention provides a water-based supramolecular adhesive material, which is prepared from raw materials including heterocyclic aromatic acyl amino acid and cationic polyelectrolyte. The raw materials are prepared in a water solvent to obtain the water-based supramolecular adhesive material.
[0038] The heterocyclic aromatic acyl amino acid comprises a heterocyclic unit with an electron-donating group, an amino aromatic carboxylic acid unit and an amino acid unit. The electron-donating group comprises an oxygen-containing electron-donating group or a nitrogen-containing electron-donating group, preferably a hydroxyl group and an amino group.
[0039] The heterocyclic unit with an electron-donating group is selected from heterocyclic units containing at least two electron-donating groups, preferably selected from nitrogen-containing heterocyclic units containing at least two electron-donating groups, and the nitrogen-containing heterocyclic unit is selected from pyridines, pyrimidines, quinolines, indoles, purines or pteridines, more preferably a nitrogen-containing fused heterocyclic unit containing two electron-donating groups, such as a pteridine ring unit containing two electron-donating groups.
[0040] The aminoaromatic carboxylic acid units are selected from aminobenzenecarboxylic acid units or aminonaphthalenecarboxylic acid units, preferably selected from aminobenzoic acid units or aminonaphthalenecarboxylic acid units, and more preferably aminobenzoic acid units.
[0041] In a preferred embodiment of the present invention, the heterocyclic aromatic acyl amino acid has the following molecular structure formula:
[0042]
[0043] in,
[0044] R1, R2, and R3 are each independently selected from hydrogen or an electron-donating group, preferably selected from hydrogen, an oxygen-containing electron-donating group or a nitrogen-containing electron-donating group, more preferably hydrogen, hydroxyl or amino. In a preferred embodiment of the present invention, one of R1, R2, and R3 is hydrogen, and the other two substituents are electron-donating groups, preferably, R3 is hydrogen, and R1 and R2 are electron-donating groups, for example, R1 is hydroxyl, R2 is amino, and R3 is hydrogen.
[0045] G1, G2, G3, and G4 are each independently selected from hydrogen, C1-C5 alkyl, C1-C5 alkoxy, amino, hydroxy, aldehyde or carboxyl, preferably selected from hydrogen, methyl, ethyl, methoxy, ethoxy, amino or hydroxy, more preferably hydrogen.
[0046] R is selected from hydrogen, alkyl, phenylalkyl, phenolic alkyl, carboxylalkyl, amide alkyl, aminoalkyl, hydroxyalkyl or nitrogen-containing heterocyclic alkyl, preferably selected from hydrogen, phenolic alkyl, carboxylalkyl, amide alkyl, aminoalkyl, hydroxyalkyl, indolyl alkyl or imidazolyl alkyl, more preferably carboxylalkyl. R has a carbon number of 0-4.
[0047] In a preferred embodiment of the present invention, the heterocyclic aromatic acyl amino acid is folic acid, that is, R1 is hydroxyl, R2 is amino, R3 is hydrogen, G1, G2, G3, and G4 are all hydrogen, and R is carboxyethyl.
[0048] Folic acid, also known as pteroylglutamic acid, is a thermodynamically stable, low-cost, slightly yellow crystalline powder. It is a naturally abundant B vitamin that can be extracted from a variety of natural foods, such as green leafy vegetables, beans, and fruits. Folic acid is vital to the human body. As one of the essential vitamins for the growth and reproduction of body cells, its deficiency will affect the normal physiological activities of the human body. This is especially important during periods of rapid cell division and growth, such as pregnancy and infancy, so a specific dose of folic acid must usually be taken every day. To date, folic acid has been widely studied due to its anti-tumor effects.
[0049] Folic acid has carboxyl, carbonyl and amide groups, which can achieve metal complexation and electrostatic interaction with other components. As a raw material for preparing adhesive materials, folic acid has a wide source and is inexpensive. So far, the application of folic acid in the field of adhesive materials has not been reported.
[0050] The cationic polyelectrolyte is selected from one or more of primary amine type cationic polymers, such as polyallylamine hydrochloride (PAH), secondary amine type cationic polymers, such as polyethyleneimine (PEI), tertiary amine type cationic polymers, such as tertiary amine type modified polyacrylamide and quaternary ammonium type cationic polymers, such as polydiallyldimethylammonium chloride (PDDA), chitosan quaternary ammonium salt (QCS), etc., preferably selected from one or more of primary amine type and tertiary amine type cationic polymers of five types of substances, including polyallylamine hydrochloride (PAH), polyethyleneimine (PEI), tertiary amine modified polyacrylamide, quaternary ammonium type cationic polymers and cationic modified polyacrylamide, cationic polyvinyl alcohol, cationized starch, cationized cellulose, and cationized chitosan, and more preferably one or more of polydiallyldimethylammonium chloride (PDDA), branched polyethyleneimine (b-PEI), chitosan quaternary ammonium salt (QCS) and polyallylamine hydrochloride (PAH), such as polydiallyldimethylammonium chloride (PDDA).
[0051] Under alkaline conditions, heterocyclic aromatic acyl amino acids are anionic and can form supramolecular bodies with cationic polyelectrolytes in aqueous solutions. Since heterocyclic aromatic acyl amino acids contain heterocyclic units with electron-donating groups, amino aromatic carboxylic acid units and amino acid units, the supramolecular bodies have adhesive force, thereby forming an adhesive material with excellent performance, which can be used for bonding various materials, including bonding biological tissues, such as human or animal organs, such as skin, metal materials, such as stainless steel, inorganic materials, such as inorganic glass, wood materials, plastics, such as polytetrafluoroethylene and polyethylene, and especially for bonding biological tissues in the field of medical surgery. When selecting and using preparation raw materials that meet the requirements of the medical field, the obtained supramolecular adhesive material can also bond biological tissues and has excellent safety, antibacterial properties and biocompatibility.
[0052] The branched polyethyleneimine contains a large number of primary, secondary and tertiary amine groups and is one of the most common and widely used cationic polymers. In addition, because it has the characteristics of good dispersion, no odor and easy recycling, and has the characteristics of low cost and easy synthesis, it has received much attention in the research of academia and industry and has applications in many fields, such as gene transport carriers in organisms, ligands and precursors of ion exchange resins, sewage treatment membranes and heavy metal ion adsorption. The weight average molecular weight of the branched polyethyleneimine is 30,000-550,000, preferably 40,000-650,000, and more preferably 50,000-750,000.
[0053] As a cationic polyelectrolyte, polyallylamine hydrochloride has the appearance of a colorless to light yellow viscous liquid. It is safe, non-toxic, soluble in water, non-flammable, has strong cohesive force, good hydrolysis stability, does not form a gel, is insensitive to pH changes, and has chlorine resistance. The weight average molecular weight of the polyallylamine hydrochloride is 30,000-110,000, preferably 40,000-90,000, and more preferably 50,000-70,000.
[0054] In the cationic polyelectrolyte of the present invention, polydiallyldimethylammonium chloride (PDDA) is a water-soluble cationic polymer with a five-membered ring structure in the main chain, and has the appearance of a colorless to light yellow viscous liquid, and has a high density of positive charges on its molecular chain, is safe and non-toxic, has strong cohesion, good hydrolysis stability, is insensitive to pH changes, and is inexpensive. It has good cohesive adsorption performance and antibacterial properties, and can be used as a building block for assembly materials in various biological and medical application fields.
[0055] The adhesive material prepared by using heterocyclic aromatic acyl amino acid and PDDA, especially folic acid and PDDA, has good adhesion and mechanical properties, and also has good safety and biocompatibility in the application in the biomedical field.
[0056] The weight average molecular weight of the polydiallyldimethylammonium chloride (PDDA) is 100,000-900,000, preferably 110,000-700,000, and more preferably 120,000-500,000. When the polymer molecular weight is less than 100,000, it is impossible to form a coagulation-type adhesive material; when the polymer molecular weight is greater than 100,000, the adhesive performance of the adhesive material increases with the increase of the molecular weight.
[0057] Chitosan, cellulose, etc., as a natural high molecular polymer, not only have good biocompatibility, but also contain highly active hydroxyl groups, which are easy to react to form cationic natural high molecular polymers. Among them, chitosan quaternary ammonium salt is one of the representative derivatives of chitosan. It is non-toxic and has high antibacterial activity. It is a relatively ideal antibacterial biomaterial and has been used to develop absorbable surgical sutures, medical dressings, artificial skin, artificial kidney membranes, etc. It is soluble in water in a wide pH range. Therefore, chitosan quaternary ammonium salt has a wide range of applications in medicine.
[0058] The supramolecular adhesive material prepared with chitosan quaternary ammonium salt as cationic polyelectrolyte and heterocyclic aromatic acyl amino acid as raw material has excellent adhesion properties and can be used for bonding various materials. It can also be used in the field of medical surgery to bond biological tissues and close surgical wounds. The adhesive material is absorbed by the human or animal body's own metabolism to meet medical needs.
[0059] The present invention also provides a method for preparing a novel aqueous supramolecular adhesive material, wherein the raw materials for preparation of the method include heterocyclic aromatic acyl amino acids and cationic polyelectrolytes, and the raw materials are dispersed in an aqueous solution for preparation. The method specifically includes the following steps:
[0060] Step 1: dissolving a heterocyclic aromatic acyl amino acid in water to obtain a solution A.
[0061] The heterocyclic aromatic acyl amino acid is added to water, stirred and mixed to dissolve the heterocyclic aromatic acyl amino acid in water to obtain solution A. Preferably, an alkaline substance is added to the aqueous solution containing the heterocyclic aromatic acyl amino acid to adjust the pH value of the solution.
[0062] The concentration of the heterocyclic aromatic acyl amino acid in the solution A is 8-120 mM, preferably 14-100 mM, more preferably 20-50 mM. The dissolution temperature is 10-40°C, preferably 20-30°C.
[0063] The alkaline substance is selected from water-soluble alkaline substances, preferably water-soluble inorganic bases, more preferably water-soluble inorganic strong bases, such as sodium hydroxide. The water is deionized water or ultrapure water, preferably ultrapure water.
[0064] The pH value of the solution A is greater than 7.2, preferably greater than 8, and more preferably 8-12.
[0065] Step 2: dissolving the cationic polyelectrolyte in water to obtain solution B.
[0066] Add the cationic polyelectrolyte into water, stir and mix, and dissolve it in the water to obtain solution B. The dissolution temperature is 10-40° C., preferably 20-30° C. The water is deionized water or ultrapure water, preferably ultrapure water.
[0067] The concentration of the cationic polyelectrolyte in the solution B is 10-120 mM, preferably 25-100 mM, and more preferably 30-50 mM. The molar amount of the cationic polyelectrolyte is measured by the molar amount of the positive charge carried by the cationic polyelectrolyte in the aqueous solution.
[0068] Step 3: Mix and stir solution A and solution B to obtain a water-based supramolecular adhesion material.
[0069] The solution A and the solution B are mixed and stirred uniformly to obtain a mixed solution containing coagulants. The mixing temperature is 10-40°C, preferably 20-30°C.
[0070] After the water solvent is separated from the mixed solution containing the condensate, the obtained condensate is washed 3-7 times with water to obtain the supramolecular adhesion material. The water is deionized water or ultrapure water, preferably ultrapure water.
[0071] The molar ratio of the heterocyclic aromatic acyl amino acid in the solution A to the cationic polyelectrolyte in the solution B is (1.6-3.0):1, preferably (1.8-2.5):1, more preferably (2.0-2.2):1. The molar amount of the cationic polyelectrolyte is measured by the molar amount of the positive charge carried by the cationic polyelectrolyte in the aqueous solution.
[0072] The present invention provides an aqueous supramolecular adhesive material, which can be prepared by simply dissolving and mixing heterocyclic aromatic acyl amino acids and cationic polyelectrolytes as raw materials, avoiding the use of toxic and harmful reagents, and having a simple preparation method and being green and environmentally friendly. The prepared aqueous supramolecular adhesive material has excellent adhesion and mechanical properties, and can be applied to the bonding of various materials. For example, by using safe, non-toxic, and biocompatible heterocyclic aromatic acyl amino acid folic acid and cationic polyelectrolyte PDDA and chitosan quaternary ammonium salt for supramolecular assembly, an adhesive material with high antibacterial properties and excellent biocompatibility is obtained, which is expected to be used in the fields of medical surgery and the like.
[0073] Example
[0074] Example 1
[0075] At room temperature, 1.1 g of folic acid was dissolved in 100 mL of ultrapure water to prepare a folic acid solution, and a 2 mol / L NaOH solution was added dropwise to adjust the pH of the folic acid solution to 9, 10, 11, and 12. 4 g of polydiallyldimethylammonium chloride (PDDA) was dissolved in 100 mL of ultrapure water to prepare a solution with a concentration of about 50 mM (i.e., a chloride ion concentration of about 50 mM).
[0076] The folic acid solutions with different pH values were mixed with the PDDA solutions in equal volumes, and after being shaken, a mixed solution containing orange-yellow coagulants was obtained. After the supernatant was removed, the folic acid-PDDA coagulants were obtained; the coagulants were washed with ultrapure water for 3 times to obtain wet folic acid-PDDA supramolecular adhesion materials: PF-C-9, PF-C-10, PF-C-11, and PF-C-12. Among them, the weight average molecular weight of PDDA is 450,000, PDDA is Aladdin reagent, Mw is 400,000-500,000, it is a PDDA aqueous solution, the mass fraction is 20wt%, and the viscosity is 800-1000CP (25°C).
[0077] It can be seen from the observation that the prepared wet folic acid-PDDA supramolecular adhesive material has a high water content and a certain fluidity, such as Figure 1 (a) shown.
[0078] The wet folic acid-PDDA supramolecular adhesive material was prepared into adhesive films: PF-C-9-Film, PF-C-10-Film, PF-C-11-Film, and PF-C-12-Film. The wet folic acid-PDDA supramolecular adhesive material was poured onto a smooth polytetrafluoroethylene plate by a casting method. After the water evaporated, a self-supporting adhesive film was formed. The macroscopic morphology of the prepared adhesive film is as follows: Figure 1 (b) as shown.
[0079] Infrared spectra of folic acid (FA), PDDA and the obtained folic acid-PDDA supramolecular adhesion film PF-C-9-Film were tested respectively. The test spectra are shown in Figure 2 As shown. Figure 2 The characteristic peak of carbonyl group at 1581 cm -1 and 1386cm -1 The characteristic peak of the pteridine ring is 1330 cm -1 , indicating that folic acid-PDDA supramolecular adhesion material was prepared by the above method.
[0080] Example 2
[0081] At room temperature, 1.1 g of folic acid was dissolved in 100 mL of ultrapure water to prepare a folic acid solution, and a 2 mol / L NaOH solution was added dropwise to adjust the pH of the folic acid solution to 9. 3.7 g of chitosan quaternary ammonium salt (QCS) was dissolved in 100 mL of ultrapure water to prepare a solution with a concentration of about 50 mM (i.e., a chloride ion concentration of about 50 mM).
[0082] The folic acid solution and the QCS solution were mixed in equal volumes, and after being shaken, a mixed solution containing brownish yellow coagulation was obtained. After the supernatant was removed, the folic acid-QCS coagulation was obtained; and the wet folic acid-QCS supramolecular adhesive material was obtained by washing with ultrapure water for 3 times. Among them, the substitution degree of QCS was 96%-98%, and QCS was purchased from MACKLIN.
[0083] The wet folic acid-QCS supramolecular adhesive material is prepared into an adhesive film: folic acid-QCS-Film. The wet folic acid-QCS supramolecular adhesive material is poured onto a smooth polytetrafluoroethylene plate by a casting method, and a self-supporting adhesive film is obtained after the water evaporates.
[0084] Example 3
[0085] At room temperature, 1.1 g of folic acid was dissolved in 100 mL of ultrapure water to prepare a folic acid solution, and a 2 mol / L NaOH solution was added dropwise to adjust the pH of the folic acid solution to 9. 4 g of branched polyethyleneimine (b-PEI) was dissolved in 100 mL of ultrapure water to prepare a solution with a concentration of about 2 mM.
[0086] The folic acid solution and the b-PEI solution were mixed in equal volumes, and after being shaken, a mixed solution containing brownish yellow coagulation was obtained. After the supernatant was removed, the folic acid-b-PEI coagulation was obtained; and the wet folic acid-b-PEI supramolecular adhesive material was obtained by washing with ultrapure water for 3 times. The weight average molecular weight of b-PEI was 50,000-750,000.
[0087] Example 4
[0088] At room temperature, 1.1 g of folic acid was dissolved in 100 mL of ultrapure water to prepare a folic acid solution, and a 2 mol / L NaOH solution was added dropwise to adjust the pH of the folic acid solution to 12. 2 g of polyallylamine hydrochloride (PAH) was dissolved in 100 mL of ultrapure water to prepare a solution with a concentration of about 50 mM (i.e., a chloride ion concentration of about 50 mM).
[0089] The folic acid solution and the PAH solution were mixed in equal volumes, and after being shaken, a mixed solution containing orange-yellow coagulants was obtained. After the supernatant was removed, the folic acid-PAH coagulants were obtained; and the wet folic acid-PAH supramolecular adhesive material was obtained by washing with ultrapure water for 3 times. Among them, the weight average molecular weight of PAH was 60,000, which was purchased from Beijing Inokai Technology Co., Ltd.
[0090] Experimental example
[0091] Experimental Example 1
[0092] The moisture content of the wet folic acid-PDDA supramolecular adhesion material prepared in Example 1 was tested, and the experimental method was as follows: first, the mass of the wet folic acid-PDDA supramolecular adhesion material was measured to be m1; then, it was dried in a vacuum drying oven at a vacuum degree of -0.1 MPa and 60°C until the mass no longer changed, at which time the mass was m2; then the moisture content = (m1-m2) / m1×100%.
[0093] The water content of PF-C-9 was 71.9%, the water content of PF-C-10 was 72.4%, the water content of PF-C-11 was 73.0%, and the water content of PF-C-12 was 73.3%.
[0094] Experimental Example 2
[0095] The PF-C-9 prepared in Example 1 was subjected to a scanning electron microscope (SEM) test. The SEM test image is as follows: Figure 1 (c) as shown.
[0096] In the SEM image, the newly prepared PF-C-9 has a porous plane, the inside of the pores is relatively smooth, and the folic acid-PDDA supramolecular adhesion material can be wetted from the side and has a certain fluidity.
[0097] Experimental Example 3
[0098] The rheological properties of the wet folic acid-PDDA supramolecular adhesion materials PF-C-9, PF-C-10, PF-C-11, and PF-C-12 prepared in Example 1 were measured using a ThermoHaake RS300 rheometer. The test method is as follows: the wet folic acid-PDDA supramolecular adhesion material is placed between a 35 mm diameter chassis and a flat turntable with a gap height of 0.1 mm; the measurement temperature is set using a Pheonix water bath through a temperature control program. In the oscillation test, the frequency is set to 0.1-100 Hz. In the shear viscosity test, the shear rate is 0.01-25 s -1 The test results are as follows: Figure 3 and Figure 4 shown.
[0099] from Figure 3 It can be seen that the loss modulus G" of the wet folic acid-PDDA supramolecular adhesive material just prepared is greater than the storage modulus G', further confirming that it has the properties of a liquid. Figure 4 The variation trend of shear viscosity with shear rate shows that it also has the property of shear thinning.
[0100] Experimental Example 4
[0101] The PF-C-9 prepared in Example 1 was used to bond glass test pieces, polytetrafluoroethylene test pieces, copper sheets, and polyethylene test pieces, and the shear adhesion strength after bonding was tested. 0.02 g of PF-C-9 was coated on the test pieces, with a coating area of 2 cm × 2 cm. Two test pieces of the same material were bonded, and then a universal tensile machine INSTRON Series 5943 (USA) was used to perform a shear test on the bonded test pieces. The maximum tensile force (unit: N) when the test pieces were separated or the adhesive layer was broken was divided by the adhesion area (cm 2 ) can be used to obtain the adhesion strength (unit: kPa).
[0102] The test results show that the shear adhesion strengths after bonding the glass specimen, polytetrafluoroethylene specimen, copper sheet, and polyethylene specimen are 138.5 kPa, 20.9 kPa, 166.6 kPa, and 32.5 kPa, respectively.
[0103] The wet folic acid-b-PEI supramolecular adhesion material prepared in Example 3 was used to bond a copper sheet, a glass specimen, polyethylene and polytetrafluoroethylene, and the shear adhesion strengths after bonding were tested to be 121.7 kPa, 559.1 kPa, 62.1 kPa and 22.2 kPa, respectively.
[0104] Experimental Example 5
[0105] The wet folic acid-PDDA supramolecular adhesive material PF-C-9 prepared in Example 1 and the PF-C-9 adhered to the copper sheet in Experimental Example 4 were tested by infrared spectroscopy. The test spectra are shown in FIG. Figure 5 shown.
[0106] from Figure 5 It can be seen from the infrared spectrum that after the copper sheet is attached, the symmetrical vibration peak of the carboxylate of PF-C-9 is 1386 cm -1 Shift to lower wavenumbers to 1380 cm -1 , indicating that the folic acid-PDDA supramolecular adhesion material produced a coordination effect after contacting with the copper sheet.
[0107] Experimental Example 6
[0108] Two wooden test pieces were bonded using the wet folic acid-PDDA supramolecular adhesion material PF-C-9 prepared in Example 1, all-purpose glue (purchased from Beijing Dehang Wuzhou Technology Co., Ltd., brand: JSENB) and 3M double-sided tape, respectively, with an adhesion area of 2.5 cm×2.5 cm, and the shear adhesion strength of the wooden test pieces was tested according to the method in Experimental Example 4. The shear adhesion strengths of the wooden test pieces bonded by PF-C-9, all-purpose glue and 3M double-sided tape were 3.56 MPa, 2.55 MPa and 0.25 MPa, respectively.
[0109] Experimental Example 7
[0110] The PF-C-9-Film obtained in Example 1 was treated to obtain adhesive films with different moisture contents, and the mechanical properties were tested using a universal tensile machine (INSTRON Series 5943 (USA)) at a tensile rate of 30 mm / min.
[0111] PF-C-9-Film was placed in different saturated salt solutions (NaBr aqueous solution, mass fraction 33%; MgCl2 aqueous solution, mass fraction 55% and NaCl aqueous solution, mass fraction 75%) for equilibrium to obtain adhesive film materials with different moisture contents: PF-C-9-Film-33%, PF-C-9-Film-55%, PF-C-9-Film-75%. The mechanical properties test results (tensile strength and elongation at break) of adhesive films with different moisture contents are shown in the figure. Figure 6 shown.
[0112] from Figure 6 It can be seen that as the moisture content of the adhesive film increases, the tensile strength of the adhesive film weakens and the elongation at break increases. The comprehensive mechanical properties of the adhesive film material can meet the needs of practical applications.
[0113] Experimental Example 8
[0114] The adhesive film PF-C-9-Film obtained in Example 1 was used to bond pigskin, and the bonding area was 2.4×2.4 cm, and the tested adhesion strength was 7.5 kPa. A tensile test was performed on the bonded pigskin using a 200 g weight. Figure 7 As shown, it can be seen that the adhesive film has a good adhesion effect.
[0115] PF-C-9-Film was used to bond wet glass and a 200 g stainless steel weight, with a bonding area of 2.4 × 2.4 cm, and excellent adhesion was also achieved, such as Figure 7 shown.
[0116] The adhesive film folic acid-QCS-Film obtained in Example 2 was used to bond pigskin, and the bonding area was 2.4×2.4 cm. A tensile test was performed on the bonded pigskin using a 5 kg weight. Figure 8 As shown, it can be reflected that the adhesive film has good adhesive strength performance.
[0117] The present invention is described in detail above in conjunction with specific embodiments and / or exemplary examples and drawings, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A water-based supramolecular adhesion material, characterized in that: The aqueous supramolecular adhesive material is prepared from raw materials including heterocyclic aromatic acyl amino acid and cationic polyelectrolyte, wherein the heterocyclic aromatic acyl amino acid has the following molecular structure formula: in, R1, R2, and R3 are each independently selected from hydrogen or an electron-donating group; G1, G2, G3, and G4 are each independently selected from hydrogen, a C1-C5 alkyl group, a C1-C5 alkoxy group, an amino group, a hydroxyl group, an aldehyde group, or a carboxyl group; R is selected from hydrogen, an alkyl group, a phenylalkyl group, a phenolic alkyl group, a carboxyl alkyl group, an amide alkyl group, an aminoalkyl group, a hydroxyl alkyl group, or a nitrogen-containing heterocyclic alkyl group.
2. The adhesive material according to claim 1, characterized in that: The heterocyclic aromatic acyl amino acid comprises a heterocyclic unit with an electron-donating group, an amino aromatic carboxylic acid unit and an amino acid unit, wherein the electron-donating group comprises an oxygen-containing electron-donating group or a nitrogen-containing electron-donating group.
3. The adhesive material according to claim 2, characterized in that: The heterocyclic unit with an electron-donating group is selected from heterocyclic units containing at least two electron-donating groups, The aminoaromatic carboxylic acid units are selected from aminobenzenecarboxylic acid units or aminonaphthalenecarboxylic acid units.
4. The adhesive material according to any one of claims 1 to 3, characterized in that The cationic polyelectrolyte is selected from one or more of primary amine type cationic polymers, secondary amine type cationic polymers, tertiary amine type cationic polymers and quaternary ammonium type cationic polymers.
5. A method for preparing the aqueous supramolecular adhesion material according to any one of claims 1 to 4, characterized in that: The preparation raw materials of the method include heterocyclic aromatic acyl amino acid and cationic polyelectrolyte, and the raw materials are dispersed in an aqueous solution for preparation. The method specifically includes the following steps: Step 1, dissolving a heterocyclic aromatic acyl amino acid in water to obtain a solution A; Step 2, dissolving the cationic polyelectrolyte in water to obtain solution B; Step 3, mixing solution A and solution B to react, to obtain a water-based supramolecular adhesion material; The molar ratio of the heterocyclic aromatic acyl amino acid in the solution A to the cationic polyelectrolyte in the solution B is (1.6-3.0):
1.
6. The method according to claim 5, characterized in that In step 1, the concentration of the heterocyclic aromatic acyl amino acid in the solution A is 8-120 mM; and the pH value of the solution A is greater than 7.
2.
7. The method according to claim 5 or 6, characterized in that: In step 2, the concentration of the cationic polyelectrolyte in the solution B is 10-120 mM, wherein the molar amount of the cationic polyelectrolyte is measured by the molar amount of the positive charge carried by the cationic polyelectrolyte in the aqueous solution.
8. Use of the aqueous supramolecular adhesion material according to any one of claims 1 to 3, characterized in that: It is used to bond biological tissues, metal materials, inorganic materials, wood materials and plastics.
9. The use according to claim 8, characterized in that Used for bonding biological tissues in the field of medical surgery.